Pengaruh Model Pembelajaran Tipe Make a Match Terhadap Motivasi Belajar Peserta Didik Pendidikan Agama Kristen dan Budi Pekerti kelas VIII SMP N 1 Pollung Tahun Ajaran 2023/2024 - Simon Lumbanbatu; Johari Manik; Hasudungan Simatupang; Andar Gunawan Pasaribu; Sandy Ariawan (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The aim of this research is to determine the positive and significant influence of the Make a Match Type Learning Model on Learning Motivation for Christian Religious Education and Character of Class VIII Students of SMP N1 Pollung for the 2023/2024 Academic Year. This research was conducted using a quantitative approach. The population is all students in class VIII of SMP N Pollung for the 2023/2024 academic year, totaling 121 people and a sample of 92 people was determined according to the Krejcie and Morgan table. Data was collected using a positive closed questionnaire with 36 items. The results of data analysis show that there is a positive and significant influence of the Make a Match Type Learning Model on Learning Motivation for Christian Religious Education and Character of Class VIII Students of SMP N1 Pollung for the 2023/2024 Academic Year: 1) Correlation Test obtained a value of rxy = 0.546 > rtable( =0.05,n=92) = 0.207, thus it is known that there is a positive relationship between variable Another(r2) =29,8 % is influenced by other factors that can increase student learning motivation. b) Test the regression equation, obtained the regression equation Y=36.99+0.52X. b) 3) Test the hypothesis using the t test to obtain tcount > ttable, namely 6.187 > 1.980. Thus, Ha is accepted and H0 is rejected.